Development of strategies for effective communication of food risks and benefits across Europe: Design and conceptual framework of the FoodRisC project - Lima Luisa; Kuttschreuter Margôt; Fletcher Jon; Verbeke Wim; Shepherd Richard; Raats Monique; Kennedy Jean; McConnon Aine; Barnett Julie; Wills Josephine; Wall Patrick (BMC, 2011)
Abstract Background European consumers are faced with a myriad of food related risk and benefit information and it is regularly left up to the consumer to interpret these, often conflicting, pieces of information as a coherent message. This conflict is especially apparent in times of food crises and can have major public health implications. Scientific results and risk assessments cannot always be easily communicated into simple guidelines and advice that non-scientists like the public or the media can easily understand especially when there is conflicting, uncertain or complex information about a particular food or aspects thereof. The need for improved strategies and tools for communication about food risks and benefits is therefore paramount. The FoodRisC project ("Food Risk Communication - Perceptions and communication of food risks/benefits across Europe: development of effective communication strategies") aims to address this issue. The FoodRisC project will examine consumer perceptions and investigate how people acquire and use information in food domains in order to develop targeted strategies for food communication across Europe. Methods/Design This project consists of 6 research work packages which, using qualitative and quantitative methodologies, are focused on development of a framework for investigating food risk/benefit issues across Europe, exploration of the role of new and traditional media in food communication and testing of the framework in order to develop evidence based communication strategies and tools. The main outcome of the FoodRisC project will be a toolkit to enable coherent communication of food risk/benefit messages in Europe. The toolkit will integrate theoretical models and new measurement paradigms as well as building on social marketing approaches around consumer segmentation. Use of the toolkit and guides will assist policy makers, food authorities and other end users in developing common approaches to communicating coherent messages to consumers in Europe. Discussion The FoodRisC project offers a unique approach to the investigation of food risk/benefit communication. The effective spread of food risk/benefit information will assist initiatives aimed at reducing the burden of food-related illness and disease, reducing the economic impact of food crises and ensuring that confidence in safe and nutritious food is fostered and maintained in Europe.